2003
DOI: 10.1021/om0300777
|View full text |Cite
|
Sign up to set email alerts
|

Bioorganometallic Chemistry:  Structural Diversity of Organometallic Complexes with Bioligands and Molecular Recognition Studies of Several Supramolecular Hosts with Biomolecules, Alkali-Metal Ions, and Organometallic Pharmaceuticals

Abstract: Bioorganometallic chemistry, a nascent area of organometallic chemistry, has recently provided significant advancements in structural diversity and molecular recognition studies. This review shows the various novel structures with bioligands of other colleagues, as well as those from our own studies. In addition, molecular recognition, the cornerstone of how biological systems operate, has now been extended to organometallic, supramolecular host molecules with biologically important guest compounds, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
153
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 334 publications
(155 citation statements)
references
References 40 publications
1
153
0
1
Order By: Relevance
“…Applications in biology and medicine are in their infancy, but the potential for exciting developments is clear (2). In the field of cancer chemotherapy, the cyclopentadienyl complex [Cp 2 TiCl 2 ] has been in clinical trials (3,4), and a ferrocene derivative of Tamoxifen is a candidate for trials for breast cancer therapy (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Applications in biology and medicine are in their infancy, but the potential for exciting developments is clear (2). In the field of cancer chemotherapy, the cyclopentadienyl complex [Cp 2 TiCl 2 ] has been in clinical trials (3,4), and a ferrocene derivative of Tamoxifen is a candidate for trials for breast cancer therapy (5).…”
mentioning
confidence: 99%
“…Applications in biology and medicine are in their infancy, but the potential for exciting developments is clear (2). In the field of cancer chemotherapy, the cyclopentadienyl complex [Cp 2 TiCl 2 ] has been in clinical trials (3,4), and a ferrocene derivative of Tamoxifen is a candidate for trials for breast cancer therapy (5). The successful design of second-and thirdgeneration platinum anticancer drugs, now widely used in the clinic, has demonstrated that detailed knowledge of the factors that control ligand substitution and redox reactions is very valuable in drug design.…”
mentioning
confidence: 99%
“…rganometallic chemistry can provide novel concepts in structural diversity and molecular recognition that can be applied to the design of pharmaceutics (1). For example, Jaouen et al (2) have designed antiestrogenic cyclopentadienyl complexes that recognize the estrogen receptor and have potential for treatment of breast cancer, and other workers have also carried out pioneering studies on the recognition of nucleobases, amino acids, and peptides by organometallic centers (1,(3)(4)(5).…”
mentioning
confidence: 99%
“…For example, Jaouen et al (2) have designed antiestrogenic cyclopentadienyl complexes that recognize the estrogen receptor and have potential for treatment of breast cancer, and other workers have also carried out pioneering studies on the recognition of nucleobases, amino acids, and peptides by organometallic centers (1,(3)(4)(5). However, as far as we are aware, there are few investigations of specific interactions of organometallic arene complexes with natural DNA (6).…”
mentioning
confidence: 99%
“…Stability is the major requirement for the biological evaluation of DNA/BSA binding interaction study, so checking the stability of the complexes in solution is very important. 30 DMSO is the most widely preferred solvent to prepare stock solutions for biophysical and biological testing. For many transition metal complexes, DMSO acts as a good ligand, coordinating with the metal center through either the sulfur or oxygen atom.…”
Section: Synthesis Of Ruthenium(ii) Schiff Base Complexesmentioning
confidence: 99%